Improving Students' Critical Thinking Skills Through Problem Based Learning in Class IV SDN 04 Talago - Risna Yanti (BiCED Proceeding, 2024)
This study aims to explore the importance of Islamic Religious Education (PAI) in shaping character and critical thinking skills in students, as well as the relevance of teaching models used in contemporary educational contexts. Several teaching models were analyzed including Problem-Based Learning (PBL), problem-based approaches, and their impact on developing critical thinking skills. Furthermore, this research highlights the role of Aqidah education and the materials related to faith in the Islamic Religious Education curriculum at both the elementary and higher education levels, as well as how philosophy-based approaches to Islamic education, such as the Ibn Khaldun model, can enhance rational reasoning and critical thinking in students. Based on various studies, this research reveals that the application of PBL and problem-based learning methods positively impacts Islamic learning outcomes and students' critical thinking skills, which are essential for preparing the 21st-century generation. This study also emphasizes the need for innovation in the design of Islamic Religious Education curricula to foster character development and reflective thinking skills in students across different educational levels.